A real-time control system for a frequency response-based permittivity sensor - Tang, Ning (Kansas State University, 2011)
Permittivity is an important property of dielectric materials. By measuring the permittivity of a material, it is possible to obtain information about the material’s physical and chemical properties, which are of great importance to many applications. In this study, a realtime control system for a frequency-response (FR) permittivity sensor was developed. The core of the hardware was a kitCON167 microcontroller (PHYTEC America, LLC), which controlled and communicated with peripheral devices. The system consisted of circuits for waveform generation, signal conditioning, signal processing, data acquisition, data display, data storage, and temperature measurement. A C program was developed in the TASKING Embedded Development Environment (EDE) to control the system. The control system designed in this study embodied improvements over a previously designed version in the following aspects: 1) it used a printed circuit board (PCB); 2) the measurement frequency range was extended from 120 MHz to 400 MHz; 3) the resolution of measured FR data was improved by using programmable gain amplifiers; 4) a data storage module and a real-time temperature measurement module were added to the system; 5) an LCD display and a keypad were added to the system to display the FR data with corresponding frequencies and to allow users to enter commands. Impedance transformation models for the sensor probe, the coaxial cable that connects the control system with the sensor probe, and the signal processing circuit were studied in order to acquire information on the permittivity of measured materials from measured FR data. Coaxial cables of the same length terminated with different loads, including an open circuit, a short circuit, a 50 resistor, and a 50 resistor paralleled by a capacitor, were tested. The results indicated that the models were capable of predicting the impedances of these specific loads using the FR data. Sensor probes with different sizes and coaxial cables with two different lengths terminated with the same sensor probe were also tested. The results were discussed. Additional tests for the gain and phase detector were conducted to compare FR data measured by the gain and phase detector with those observed on an oscilloscope. The results were discussed.
Keywords: Permittivity; Frequency response; Sensor; Circuit design; Independence modeling; Agriculture, General (0473)